Synthesis and Crystal Structure of 5,5’-Dinitro-2,2’-[(1,4-butylene)dioxybis(nitrilomethylidyne)]diphenol - Wang, Li; Sun, Yin-Xia; Dong, Xiu-Yan; Zhao, Li; Xu, Li (Asian Journal of Chemistry, 2013)
The compound, 5,5'-dinitro-2,2'-[(1,4-butylene)dioxybis(nitrilomethylidyne)]diphenol, was synthesized by the reaction of 5-nitrosalicylaldehyde with 1,4-bis(aminooxy)butane in ethanol and characterized structurally by single crystal X-ray diffraction method. The molecule lies across a crystallographic inversion centre and assumes a Z configuration with respect to the C=N bond. The strong intramolecular O3-H3···N1 and O6-H6···N2 hydrogen bonds play an important role in the stability for the crystal structure of 5,5'-dinitro-2,2'-[(1,4-butylene)dioxybis-(nitrilomethylidyne)]diphenol. It is noteworthy that the two benzene rings of present compound form a dihedral angle of 6.59 (3) Å and the distance between the two intramolecular benzene rings is 3.701 (2) Å, revealing weak intramolecular p-p stacking interaction along b axis.